Growth performance and grain yield of soybean (Glycine max) grown at different planting density - Rajab, Mohd Arif (2015)
Planting density influences crop performance and the quality and quantity of soybean yield. This study was conducted to evaluate planting density on soybean growth and grain yield. In this study, soybean of Dieng cultivar was grown under field conditions. The treatment included three different planting density; 15 seeds, 30 seeds (control) and 50 seeds per meter. Plant samplings were done weekly from V1 stage (first trifoliate) to stage R7 (physiological maturity stage). Soybean plants were harvested to determined yield components at R8 (fully maturity stage). There was a significant difference (P<0.05) between fresh and dry grain weight when planted at different planting density. In this study, differences in the total seed yield was observed when planted at different plant densities in crop growth and seed yield which also related to crop competition at different population density. Planting density at 30 seeds per meter (control) had the highest fresh weight. Soybean planted at 30 seed m-1 was found to be an optimum planting density for the soybean.